2011
DOI: 10.1111/j.1467-7652.2010.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically engineered soybean seed with enhanced threonine levels: biochemical characterization and seed‐specific expression of lysine‐insensitive variants of aspartate kinases from the enteric bacterium Xenorhabdus bovienii

Abstract: SummaryThreonine (Thr) is one of a few limiting essential amino acids (EAAs) in the animal feed industry, and its level in feed rations can impact production of important meat sources, such as swine and poultry. Threonine as well as EAAs lysine (Lys) and methionine (Met) are all synthesized via the aspartate family pathway. Here, we report a successful strategy to produce high free threonine soybean seed via identification of a feedbackresistant aspartate kinase (AK) enzyme that can be over-expressed in develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 44 publications
0
20
0
1
Order By: Relevance
“…A recent study showed that seed-specific expression of the feedback-resistant variants of aspartate kinases could result in up to 100-fold increase in free threonine in transgenic soybean seeds (Qi et al 2011). Interestingly, these soybean plants also accumulated increased levels of methionine, lysine, and isoleucine resulting in an upto 3.5-fold increase in the total free amino acid content; however, this study did not examine if there was also any increase in the levels of protein-bound essential amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that seed-specific expression of the feedback-resistant variants of aspartate kinases could result in up to 100-fold increase in free threonine in transgenic soybean seeds (Qi et al 2011). Interestingly, these soybean plants also accumulated increased levels of methionine, lysine, and isoleucine resulting in an upto 3.5-fold increase in the total free amino acid content; however, this study did not examine if there was also any increase in the levels of protein-bound essential amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…This eventually helps to manipulating the biosynthesis of amino acid to increase the amino acid content and nutritive value in crops. Recently, much work has been done to metabolically engineered crops and grains with enhanced amino acid levels [42], [43]. Thirdly, the mechanism of structural transition to tetramer assembly is similar way to the other three different crystallographic environments.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, a >100-fold increase of free lysine and 5-fold increase of total seed lysine content was observed. More recently, soybeans showing enhanced threonine levels have been engineered using seed-specific expression of lysine-insensitive variants of aspartate kinases from bacteria [58]. This strategy produced transgenic soybeans with a 100-fold increase in threonine levels and 3.5-fold increase in total free amino acid content without negative impacts on seed morphology or germination.…”
Section: Dietary Amino Acidsmentioning
confidence: 99%